Coaching the power clean: A constraints-led approach. - Verhoeff, W. J.; Millar, S. K.; Oldham, A. R. H.; Cronin, J. (Strength and Conditioning Journal, 2020)
Traditionally, strength and conditioning coaches have used explicit instructions when changing movement behavior. Recent work has questioned the efficacy of this approach. Whether explicit instruction is best for facilitating movement change is discussed along with an alternative approach. A brief review of traditional coaching methods is undertaken, highlighting differences between the traditional "coach-centered approach" and an "athlete-centered, constraints-led approach." The constraints-led approach is applied to coaching the power clean. This provides an example of how strength and conditioning practitioners may approach the coaching of movement using methods that align with contemporary coaching as well as skill acquisition theory.